Quality of Sleep in Urban and Aeronautical Firefighters of Ciudad Bolívar, Venezuela - Rincon Ortiz, Mishel Yohana (2024)
Introduction: Night work increases the state of fatigue and the deterioration of biological functions, affects mental and physical health, causing poor work performance, the objective of the study was to determine the quality of sleep and the sociodemographic data related to the body staff. of urban firefighters and the aeronautical fire department of Ciudad Bolívar Venezuela. Methodology: An observational, cross-sectional study with a quantitative approach was carried out. The population was made up of 60 urban firefighters and 20 aeronautical firefighters, the sample was by convenience, through a self-administered survey, sociodemographic data, working conditions and the Pittsburgh Sleep Quality Index (ICSP) were collected. Descriptive statistics and Fisher's exact test were applied. Results: It was found in urban firefighters that 61.82% presented pathological sleep quality, the most affected gender was male, and the highest frequency of pathological sleep were those who had service time between 1-11 years. Of the aeronautical firefighters, 83.33% presented pathological sleep, with the highest frequency being pathological sleep; It was the masculine gender. It was also observed that the subjective quality of sleep is “quite good” in both. Conclusions: Both firefighters present alterations in sleep quality, with urban firefighters being the most affected. It was found that there are differences in relation to age, gender, and length of service. The importance of adapting to the pace of work was also evident. coping tools.